The acceptance of halal food in non-Muslim countries: Effects of religious identity, national identification, consumer ethnocentrism and consumer cosmopolitanism. Issue 4 (9th April 2019) - Wilkins, Stephen; Butt, Muhammad Mohsin; Shams, Farshid; Pérez, Andrea
Abstract : Purpose: International restaurant and fast food chains such as KFC, McDonald's and Subway currently serve halal food in some non-Muslim countries, with mixed results. The purpose of this paper is to identify the factors that most influence the product judgements of halal food amongst non-Muslim consumers in non-Muslim countries and to assess the extent to which these judgements are related to willingness to consume halal food. Design/methodology/approach: A quantitative survey method was adopted, using a total sample of 1, 100 consumers in Canada, Spain and the UK. The proposed model was tested using structural equation modelling. Findings: The results suggest that it may be possible for firms to satisfy specific niche market segments with standardised mass market products. Consumer cosmopolitanism and non-Muslim religious identity were found to be positively related to halal product judgement, and consumer ethnocentrism and national identification were negatively related to halal product judgement. There was a strong relationship between product judgement and willingness to consume halal food. Practical implications: The findings indicate that halal marketing may provide promising business opportunities for international restaurant and fast food chains, as well as food manufacturers and retailers. However, in countries or regions where there are many consumers with high levels of national identification or consumer ethnocentrism, firms should not expect non-target consumers to accept halal products. Originality/value: This is the first study to suggest that, in non-Muslim countries, food companies may switch entirely to halal produce for certain products as an effective market segmentation strategy targeting Muslim consumers.